2011
DOI: 10.1245/s10434-011-1987-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Curatively Resected pT4b Gastric Cancer with Respect to Invaded Organ Type

Abstract: In pT4b gastric cancer, pancreatic invasion was found to portend the least favorable prognosis, especially in cases requiring pancreaticoduodenectomy. However, prognoses were more favorable after curative resection in patients without advanced lymph node stages (N2, N3a, and N3b), an encircling type of gastric tumor, or pancreatic invasion. We propose a novel therapeutic strategy for patients with T4b gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 22 publications
2
23
1
Order By: Relevance
“…Min et al 16 exclude from the multivisceral resection patients with lymph node metastasis in the para-aortic chain and those who would require associated duodenopancreatectomy. There are also trends in the literature 19 that suggest neoadjuvant treatment, either with chemotherapy or with chemotherapy + radiotherapy, in order to promote tumors' downstaging and to evaluate the biological response -in case of disease progression, patients would be spared from extensive surgery without therapeutic benefit.…”
mentioning
confidence: 99%
“…Min et al 16 exclude from the multivisceral resection patients with lymph node metastasis in the para-aortic chain and those who would require associated duodenopancreatectomy. There are also trends in the literature 19 that suggest neoadjuvant treatment, either with chemotherapy or with chemotherapy + radiotherapy, in order to promote tumors' downstaging and to evaluate the biological response -in case of disease progression, patients would be spared from extensive surgery without therapeutic benefit.…”
mentioning
confidence: 99%
“…Although Min et al [16] reported the lowest complication rate of 22% among the reported rates of the previous studies, they also demonstrated one of the highest mortality rates, which was 11%. These results meant that half of the patients who suffered from postoperative complications died; this 50% mortality rate among patients who suffered postoperative morbidity seemed to be a bit high, which was possibly due to the variable definitions of all the complications.…”
Section: Short-term Surgical Outcomesmentioning
confidence: 82%
“…When Buchholtz et al [7] first reported PD for gastric cancer in 1978, they concluded that this treatment should not be performed because of the unacceptable risk without an additional and greater degree of palliation or likelihood of cure; however, they did not discuss their reasons in detail. Several studies have demonstrated short-term surgical outcomes of PD, including intraoperative blood loss, operation time, morbidity, and mortality [ Table 1] [8][9][10][11][12][13][14][15][16][17] . The median amount of blood loss was reported to be > 1000 mL and the median operation time was as long as 7 h.…”
Section: Short-term Surgical Outcomesmentioning
confidence: 99%
See 2 more Smart Citations